Sectarian order in Bahrain : the social and colonial origins of criminal justice - Strobl, Staci (Lexington Books, 2018)
Through the lens of a new interpretation of criminal justice history Sectarian Order in Bahrain focuses on a cache of colonial criminal cases dated 1924 to 1940. It outlines major shifts in notions of the social order, highlighting a sectarianism modus operandi within the colonial criminal justice system.